A representação da informação Arquivística: Uma Análise do discurso teórico e institucional a partir dos contextos Espanhol, Canadense e Brasileiro - Barros, Thiago Henrique Bragato [UNESP] (2014)
The Discourse Analysis is a discipline that has theoretical and methodological characteristics that may contribute to the growth of Archival Science theory, because, is through the statements game permeate by ideological positions placed on the social-historical process, the text (oral and written) is produced, ie, the Archival Science related to discursive and ideological formations that are often suppressed in their discursive instances. The problem sets in a systematic search and identify the differences and similarities between archival institutional practice and theory on the present time. In this sense, we seek to characterize as the archival discourse is constructed and behaves in academic and institutional professional spheres in contemporary society. By analyzing the concepts Archival Representation and description today by three streams that were selected (Brazilian, Canadian and Spanish) at the level of his theory, at the academic level and how they are worked in archival institutions these countries. Thus, we objectives through the theoretical and methodological framework of discourse analysis to understand how they behave and build and how these notions are used in theory and practice of the Archival Science seeking a conceptual and discursive construction for the discipline. This analysis takes place from the leading theorists of these currents and archival institutions most important of these countries in the case, the National Archives. We find some possible discursive formations in Archival Science one related to traditionalism and another related to reformism was found. We conclude that the Archival Science has a complex possess of discursive formations built over its institutional and theoretical history